Proposal of Intelligent Routes for the Food Processing and Marketing Centers (Cepromas) of the Guatuso and Upala Zones, Costa Rica - Barboza Navarro, David (2018)
Food Processing and Marketing Centers (Cepromas) were created in 2008 by the Costa Rican Government in areas of high socioeconomic vulnerability and are managed by small producer’s organizations; with the main purpose of improving rural economy and food availability, in addition of developing innovative ideas. There are at least seven Cepromas that process beans in Costa Rica, located in the North Area, the South Area and the Chorotega Region, being the North Area the one with the biggest harvest nationwide. Therefore, the main objective of this research is to determine a system of smart transportation routes, where the Cepromas of San Blas, La Palmera and Llano Bonito become a single processing and distribution company of 100% Costa Rican beans in different markets around the country. To define the lowest cost routes between the processing centers and the target markets, the Vogel Approach Method was implemented, based on the principles of linear programming; in addition, the respective potential demand from the markets of interest and the potential supply by Cepromas were estimated. Among the results obtained, the need to buy beans from Cepromas of the Southern Zone by the Cepromas of the Northern Zone in order to avoid a shortage when the province of Alajuela is not in production season was identified and labeled as a very important factor; in addition, the necessary investments in vehicles for transportation were determined and transporting costs were estimated ranging between ₡6,974 and ₡17,378 per ton depending on the season.